USE OF LIPPIA SCABERRIMA ESSENTIAL OIL TO PROMOTE POSTHARVEST QUALITY OF SUBTROPICAL FRUITS - Combrinck, S.; Renier, T.; du Plooy, W.; Botha, B. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Lippia scaberrima Sond. is an aromatic shrub occurring in semi-arid, summer-rainfall grassland in Gauteng, the Free State and North West provinces of South Africa. In this study, the essential oil of bulk samples of L. scaberrima growing in a natural habitat were evaluated for their antifungal activity against common commercially important postharvest pathogens of subtropical fruits. The oil was found to exhibit strong in vitro activity against post-harvest spoilage pathogens of mango, avocado and citrus fruit. GC-FID analysis of the oil allowed identification of limonene, 1,8-cineole and R-carvone as the main constituents. Antifungal activity of the oil was attributed to the presence of R-carvone. These results were evaluated by semi-commercial and commercial trials using fruits treated postharvest with coatings amended with essential oil. The control treatments were done using standard commercial fungicide applications, while the experimental treatments all consisted of coatings amended with the various oils and terpenoids, without the inclusion of synthetic fungicides. Effective disease control was obtained from all of the amended treatments. In addition, the overall quality of the fruits was maintained. Results obtained indicate that the essential oil of L. scaberrima and selected terpenoids can be used as alternatives to synthetic chemical compounds in the postharvest treatment of fruit. Suitably amended coatings are currently being commercialised.